The long noncoding RNA LUCAT1 regulates endometrial receptivity via the miR-495-3p/S100P axis - Junyu Shang; Yumei Chen; Qianwen Jiang; Wenxin Li; Minjun Lu; Jiamin Zhou; Li Lin; Jie Xing; Mengxue Zhang; Shijie Zhao; Jingjing Lu; Xuyan Shi; et al. (Communications Biology)
Abstract Recently, interest in investigating the effects of long noncoding RNAs (lncRNAs) on endometrial receptivity (ER) has increased within the field of assisted reproductive technology. Therefore, the objective of this study is to identify and analyze the role of the lncRNA LUCAT1 and to elucidate its specific mechanism in regulating ER. Hub genes associated with ER are identified via Weighted gene co-expression network analysis (WGCNA) in two datasets downloaded from the GEO database. These hub genes identified via WGCNA were subsequently validated. The combination of a dual-luciferase assay, qRT‒PCR, western blotting, and other techniques are used to investigate the molecular mechanism by which LUCAT1 regulates S100P. In this study, LUCAT1 expression is shown to significantly affect ER, and the depletion of LUCAT1 leads to impaired ER function. Additionally, LUCAT1 is shown to act as a molecular sponge for miR-495-3p, thereby modulating the expression of S100P. This modulation influences the proliferation, migration, and invasion capabilities of Ishikawa cells, as well as the adhesion of JAR cells to endometrial cells. Therefore, LUCAT1 can regulate ER via the miR-495-3p/S100P axis, which provides experimental evidence for the identification of innovative strategies aimed at enhancing endometrial receptivity.